Hybrid controller for swinging up inverted pendulum system - Nundrakwang, Songmoung; Benjanarasuth, Taworn; Ngamwiwit, Jongkol; Komine, Noriyuki (My University, 2005)
A hybrid controller for swinging up inverted pendulum system is proposed in this paper. The controller composes of two parts. The first part is the PD position control for swinging up the pendulum from the natural pendent position by moving the cart back and forth until the pendulum swings up around the upright position. The second part is a servo state feedback control designed by LQR which will be switched to stabilize the inverted pendulum in its upright position. The effectiveness and reliability of the proposed hybrid controller for swinging up inverted pendulum on cart are also shown by the experimental results. © 2005 IEEE.
Keywords: Inverted pendulum; Linear quadratic regulator; PD position control; Swinging-up control